Bioaccumulation of Perfluorinated Alkyl Acids: Observations and Models - Ng, Carla A; Hungerbühler, Konrad (Environmental science & technology, 2014)
In this review, we consider the two prevailing hypotheses for the mechanisms that control the bioaccumulation of perfluorinated alkyl acids (PFAAs). The first assumes that partitioning to membrane phospholipids, which have a higher affinity for charged species than neutral storage lipids, can explain the high bioaccumulation potential of these compounds. The second assumes that interactions with proteinsincluding serum albumin, liver fatty acid binding proteins (L-FABP), and organic anion transportersdetermine the distribution, accumulation and half-lives of PFAAs. We consider three unique phenomena to evaluate the two models: (1) observed patterns of tissue distribution in the laboratory and field, (2) the relationship between perfluorinated chain length and bioaccumulation, and (3) species- and gender-specific variation in elimination half-lives. Through investigation of these three characteristics of PFAA bioaccumulation, we show the strengths and weaknesses of the two modeling approaches. We conclude that the models need not be mutually exclusive, but that protein interactions are needed to explain some important features of PFAA bioaccumulation. Although open questions remain, further research should include perfluorinated alkyl substances (PFASs) beyond the long-chain PFAAs, as these substances are being phased out and replaced by a wide variety of PFASs with largely unknown properties and bioaccumulation behavior.